Use of a criteria‐based audit to optimize uptake of cesarean delivery in a low‐resource setting. Issue 2 (17th December 2018) - Mgaya, Andrew H.; Kidanto, Hussein L.; Nyström, Lennarth; Essén, Birgitta
Abstract: Objective: To evaluate the impact of a criteria‐based audit (CBA) of obstructed labor and fetal distress on cesarean delivery and perinatal outcomes. Methods: A cross‐sectional study was performed at a tertiary referral hospital in Tanzania. Data were collected before and after CBA (January 2013–November 2013 and July 2015–June 2016). Outcomes of fetal distress (baseline CBA, n=248; re‐audit, n=251) and obstructed labor (baseline CBA, n=260; re‐audit n=250) were assessed using a checklist. Additionally, 27 960 parturients were assessed using the Robson classification. Results: Perinatal morbidity and mortality decreased from 42 of 260 (16.2%) to 22 of 250 (8.8%) among patients with obstructed labor after CBA ( P =0.012). Cesarean delivery rate decreased for referred term multiparas with induced labor or prelabor cesarean delivery (odds ratio [OR] 0.28, 95% confidence interval [CI] 0.09–0.82). Cesarean delivery rate for preterm pregnancies increased among both referred (OR 1.28, 95% CI 1.02–1.63) and non‐referred (OR 2.78, 95% CI 1.98–3.90) groups. Neonatal distress rate decreased for referred term multiparas (OR 0.72, 95% CI 0.56–0.92), referred preterm pregnancies (OR 0.32, 95% CI 0.25–0.39), and non‐referred preterm pregnancies (OR 0.26, 95% CI 0.18–0.36). Conclusion: Use of CBA reduced poor perinatal outcomes of obstructed labor and increased uptake of cesarean delivery. Abstract : Criteria‐based audit and the Robson classification were useful tools for monitoring and optimizing the uptake of cesarean delivery in a low‐resource setting.